Pine pollen for molecular encapsulation and oral delivery applications - Prabhakar, Arun Kumar (2018)
Molecular delivery using carriers for biological applications has been a subject of interest for the past many years, as some molecules suffer from solubility (reduced bioavailability) and stability (pH & enzyme-sensitive molecules like proteins) issues, resulting in denaturation, inactivation & loss of function. This necessitates a robust delivery vehicle, capable encapsulating such molecules, protecting them till the site of release, followed by controlled tunable release as to avoid low or excess levels, keeping the molecular concentration in the effective therapeutic window, especially in case of drug delivery. Various nano and microparticles of different sizes and surface chemistry have been used for such delivery through different modes of administration with oral being most favoured, due to ease of dosage, along with high patient compatibility. Most of these particles are synthetic in nature, involving multiple processing steps and suffer from issues like largescale synthesis, non-uniformity, particle stability (under gastric conditions etc), biocompatibility & biodegradability to name some pressing issues. Few natural and bioinspired carriers, which have relatively much lesser safety concerns, have also been explored for this purpose successfully, which pushes us to look at other such naturally available resources. Plant pollen and spores, a natural product with uniform size, physicochemical characteristics proves to be invaluable in this aspect, offering molecular loading and protection for oral delivery applications, with promising research done till date. Pollen and spores have been shown to be promising prospects for encapsulating molecules due to their double layered wall, comprising of a cellulosic intine and a exine, composed of a supreme polymer called sporopollenin. Processed pollen namely, sporopollenin exine capsules (SECs), where pollen/spores are subject chemical treatment to remove sporoplasmic contents and the intine layer, were favoured due to lower allergenicity and more loading space, with most of the work focused on singlecompartmental non-saccate pollen (Lycopodium, Sunflower etc.). Here we show that multi-compartmental pine pollen is also an effective vehicle to encapsulate and deliver molecules of interest. It has been consumed as a super- food with health-benefits such as enhanced immune and endocrine function (excellent source of testosterone), lowering of cholesterol levels along with anti-inflammatory, anti-arthritic, and anti-tumor activity and has not been explored for molecular encapsulation till date. Pine SECs however have beenproduced by sequential organic solvent, acid/base and enzymatic processing, with no process optimization nor morphological characterisation done, followed by loading of a few molecules. Here we looked at pine SECs got through acid-processing of defatted pine pollen intially, with various processing conditions like acids, concentrations and duration were explored, with the structural integrity of the capsules looked into for every processing condition with defatted pine as the source material. Given the rapid rise in protein therapeutics, SEC production was followed by protein (BSA) loading, where it was found to load thrice as much as defatted pollen of the same mass, with fluorescently tagged proteins (FITC-BSA) used to analyse the spatial loading. As the SECs suffered from structural issues, natural and defatted pollen( which involves relatively less processing) was explored more in detail in the next study, where natural pine pollen was ether-defatted. Natural pine pollen was process optimized for BSA encapsulation regarding the loading method (passive or vacuum-assisted loading), loading duration and protein concentration and then comparitive protein (BSA) loading of natural with defatted pine pollen was done to quantify protein loading with the degree of defatting. Defatted pine loaded better here due to increased pore size as measured by nitrogen adsorption/desorption isotherms. Controlled release was shown using BSA-loaded defatted pollen as the carrier, with natural polymers as binders (Xanthan Gum) or using coatings (Sodium Alginate) with tableted formulations, with simulated gastric (pH 1.2) and intestinal fluids (pH 7), where the protein was protected in the gastric phase and released gradually in the intestinal phase. FITC-BSA loading showed that the protein loaded mainly into the air-sacs with minimal central cavity loading with vacuum loading for both natural and defatted pollen, which is different from SECs spatial loading pattern, which loaded all over the particle. Finally, natural pine pollen was explored for loading of other potential molecules like dyes and drugs apart from proteins (BSA & IgG) also, through simple passive loading and vacuum–assisted loading, where the large proteins were found to load exclusively in the air-sacs with vacuum loading and minimally into the central cavity with passive loading. The dyes and drugs however loaded into the central cavity alone irrespective of the loading method. This was followed by dual molecular loading, where the dyes and drug were loaded into the central cavity through passive loading, followed by vacuum loading of BSA, which resulted in compartmentalization (distinct molecular loading pattern into air-sacs and central cavity) of molecules. The protein structure of BSA was checked into pre-loading and post-release and was found to be conserved. All this show that pine pollen is capable of encapsulating, preserving and controlled-release of proteins and other molecules, opening up myriad applications in fields like drug delivery, molecular preservation, nutraceutical delivery etc.